Dental cleaning materials
The dental cleaning material, composed of water and water-soluble silicate, addresses the challenge of removing adhesive inhibitors from dental surfaces by providing effective cleanability and biosafety, thereby improving the adhesion strength of dental materials.
Patent Information
- Application Number
- JP2023168926
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Current dental cleaning materials face challenges in effectively removing adhesive inhibiting components like proteins from dental tissues and prosthetic restorations, especially from zirconia and metal surfaces, while ensuring biosafety and adequate cleanability.
A dental cleaning material comprising water and water-soluble silicate, which provides excellent cleaning properties and biosafety by effectively removing contaminants through alkalinity and colloidal action, without the irritancy of strong alkalines.
The material achieves excellent cleanability and biosafety, effectively removing proteins and other contaminants from dental surfaces, thereby enhancing the adhesion strength of dental adhesives and cements.
Smart Images

Figure 2025058782000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental cleaning material that can be used on dentin and dental prosthetic restorations. [Background technology]
[0002] In the field of dentistry, indirect restoration is used to bond a prosthetic device made of dental ceramics or metal to the defect site, and direct restoration is used to fill the defect site with a dental composite resin. When body fluids such as saliva or blood adhere to the dentin or the attachment surface of the prosthetic device during these treatments, components such as proteins contained in the body fluids adhere to the attachment surface, and it is known that the adhesiveness of dental adhesives and dental cements to the prosthetic device or dentin decreases. Among them, proteins are known to specifically adsorb to the dentin surface and zirconia surface, and are difficult to remove. Removing adhesion inhibitors such as proteins from the attachment surface is an important operation for repairing the defect site, but it is complicated because appropriate treatment is required depending on the material of the attachment surface.
[0003] Cleaning methods for removing adhesion-inhibiting components include spraying with water from a three-way syringe used in dental treatment and ultrasonic cleaning, but these methods have been shown to be insufficient in removing surface contamination (Non-Patent Documents 1 and 2). A method is known in which the prosthetic device itself is removed by sandblasting, but if the prosthetic device is subjected to this treatment after a try-in to confirm its compatibility with the defect, the surface will be scraped off and its compatibility will decrease, making it clear that precise treatment cannot be performed.
[0004] Another method proposed is the application of sodium hypochlorite, which has been shown to sufficiently remove surface contamination and sufficiently restore adhesive strength, but the sodium hypochlorite itself is irritating to the living body. Another widely known method is to remove body fluid contamination by cleaning with phosphoric acid. Although this method is sufficient for cleaning prosthetic devices made of glass ceramics, hard resin, etc., when applied to prosthetic devices made of zirconia or metal, the phosphate group chemically bonds to the surface, which acts as an inhibitor and reduces adhesiveness, which is an issue (Non-Patent Documents 1 and 2).
[0005] Patent Document 1 describes a tooth cleaning material containing a strong alkaline component such as sodium hydroxide, along with its method of use, but because it contains an extremely strong alkaline material as a cleaning component, it cannot be used in the oral cavity from a safety standpoint. Patent Document 2 describes a tooth cleaning material containing a surfactant formed from an acidic group-containing radical polymerizable monomer and a salt of an organic amine compound, and although it can be used in the oral cavity, there is room for improvement in terms of cleaning ability against proteins adsorbed on the surface to be attached.
[0006] Another issue is that the method of use for dental cleaning products is explained through step cards and user manuals, which does not adequately communicate the proper method of use, and because substances such as proteins cannot be seen, users cannot experience the cleaning properties of the products. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5607559 [Patent Document 2] JP 2020-83872 A [Non-patent literature]
[0008] [Non-Patent Document 1] Efficacy of various cleaning solutions on saliva-contaminated zirconia for improved resin bonding(J. Adv Prosthodont ,2015;7:85-92 Da-Hye Kim, Jun-Sik Son, Seong-Hwa Jeong, Young-Kyung Kim, Kyo-Han Kim, Tae-Yub Kwon) [Non-Patent Document 2] The effect of different cleaning agents on saliva contamination for bonding performance of zirconia ceramics(Dental Materials Journal, 37(5) · September 2018 Akifumi TAKAHASHI, Tomohiro TAKAGAKI, Takahiro WADA, Motohiro UO, Toru NIKAIDO and Junji TAGAMI) Summary of the Invention [Problem to be solved by the invention]
[0009] The above cleaning materials have room for improvement in terms of cleaning ability and biological safety, and an object of the present invention is to provide a dental cleaning material that combines excellent cleaning ability and biological safety.
[0010] Another object of the present invention is to convey to a user the proper method of use through the use of the demonstration kit, and to enable the user to visually confirm the cleaning properties and thus experience the usefulness of the kit. [Means for solving the problem]
[0011] As a result of intensive research to solve the above problems, the inventors have found a dental cleaning material that has high biological safety and excellent cleaning properties by incorporating a water-soluble silicate (b) as a cleaning component, and have completed the present invention. That is, the present invention provides a dental cleaning material containing water (a) and a water-soluble silicate (b). Effect of the Invention
[0012] According to the present invention, a dental cleaning material having both excellent cleaning properties and biological safety can be provided. [Brief description of the drawings]
[0013] [Figure 1] 1A is a diagram showing the protein-stained test specimen before treatment, and FIG. 1B is a diagram showing the protein-stained test specimen after treatment with the cleaning material 1. FIG. [Diagram 2] FIG. 13 is a diagram showing a zirconia test specimen after only one half of the surface has been treated with cleaning material 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The dental cleaning material of the present invention will be described in detail below. The dental cleaning material of the present invention contains water (a) and a water-soluble silicate (b).
[0015] The water (a) in the present invention is used as a solvent for homogenizing various components, and therefore, distilled water or ion-exchanged water that is substantially free of harmful impurities for medical use is preferred.
[0016] The amount of water (a) is preferably 50-99.5% by mass, more preferably 90-99.5% by mass, of the dental cleaning material. If the amount of water is less than this range, it may not be compatible with the tooth structure and the cleaning ability may decrease, while if the amount is more than the above range, it may have a lower affinity with body fluids, especially proteins, and the cleaning ability may decrease. The amount of water (a) may be the balance of other components in the dental cleaning material.
[0017] The water-soluble silicate (b) is an alkali metal salt of silicic acid, and those that exhibit water solubility can be used without restrictions. The water-soluble silicate (b) can be, for example, an alkali metal salt of silicic acid composed of M2O (M is an alkali ion) and SiO2. In this case, the molar ratio (SiO2 / M2O) of M2O to SiO2 of the water-soluble silicate (b) can be 0.5 to 4.0. In this specification, the molar ratio represents the ratio of the silicon component to the alkali component represented by SiO2 / M2O (M = alkali ion), and the alkalinity when the aqueous solution is formed is stronger as the molar ratio is smaller. The water-soluble silicate liberates the contaminant by causing potential repulsion between the adhesion surface and the contaminant due to the alkalinity of the aqueous solution, and prevents the adhesion of the contaminant by colloidal action. Compared with alkali metal hydroxides that are generally used as alkaline agents, it is less irritating to the living body and is highly safe. In this specification, water solubility refers to a solubility in water of 5 g / 100 mL or more at 25°C, and any silicate that dissolves within the range of the composition of the dental cleaning material of the present invention can be used without restrictions. The dental cleaning material of the present invention can contain only an alkali metal salt of silicic acid composed of M2O (M is an alkali ion) and SiO2 as the water-soluble silicate (b).
[0018] The alkali metal salt of silicic acid composed of MO (M is an alkali ion) and SiO2 may have alkali ions such as sodium, potassium, lithium, strontium, aluminum, and magnesium. Water-soluble silicates containing sodium, potassium, or lithium as alkali ions are preferred. Specific examples of sodium silicate include sodium orthosilicate (molar ratio 0.5), sodium metasilicate (molar ratio 1.0), sodium sesquisilicate (molar ratio 1.6), sodium silicate No. 1 (molar ratio 2.0 to 2.2), sodium silicate No. 2 (molar ratio 2.4 to 2.6), sodium silicate No. 3 (molar ratio 3.0 to 3.2), sodium silicate No. 4 (molar ratio 3.9 to 4.1), sodium silicate No. 5 (molar ratio 3.6 to 3.9), etc.; examples of potassium silicate include potassium orthosilicate (molar ratio 0.5), potassium metasilicate (molar ratio 1.0), potassium sesquisilicate (molar ratio 1.6), potassium silicate (molar ratio 2 to 4), etc.; and examples of lithium silicate include lithium silicate (molar ratio 4.2 to 7.0), etc., which may form a hydrate. When the molar ratio is small, the alkalinity is strong and the cleaning effect is high, but the irritation to the living body may be strong. On the other hand, when the molar ratio is large, the cleaning effect may be low, so the molar ratio is preferably in the range of 0.5 to 4.0, and more preferably in the range of 1.0 to 3.5.
[0019] In the dental cleaning material of the present invention, these water-soluble silicates (b) may be used alone or in combination of two or more. When the dental cleaning material of the present invention contains two or more water-soluble silicates (b), the weighted average value calculated from the molar ratio and blending ratio of each water-soluble silicate (b) is preferably 0.5 to 4.0.
[0020] The amount of the water-soluble silicate (b) is appropriately determined because the degree of alkalinity varies depending on the molar ratio. The amount is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%. If the amount of the water-soluble silicate (b) is less than this range, the cleaning properties may decrease. If the amount is more than the above range, the irritation to the living body may tend to be strong.
[0021] The dental cleaning material of the present invention preferably has a pH of 10 to 13. If the pH is less than 10, cleaning properties may be poor, and if it exceeds 13, irritation to the living body may be strong.
[0022] The dental cleaning material of the present invention can contain a surfactant (c) to improve cleaning performance by imparting a surfactant effect. The surfactant is not particularly limited as long as it has a surfactant function, and any known compound that is generally used can be used without any restrictions. The surfactant can be a cationic surfactant, an amphoteric surfactant, an anionic surfactant, a nonionic surfactant, etc.
[0023] Specific examples of the cationic surfactant include quaternary ammonium salts, primary amine salts, secondary amine salts, tertiary amine salts, quaternary amine salts, and pyridine derivatives.
[0024] Specific examples of amphoteric surfactants include betaine type surfactants, carboxylic acid derivatives, and imidazoline derivatives.
[0025] Specific examples of anionic surfactants include alkyl phosphate surfactants, sulfated oils, soaps, sulfated ester oils, fatty alcohol sulfate salts, alkyl sulfate salts, fatty acid ethyl sulfonates, alkylbenzene sulfonates, and phosphate salts.
[0026] Specific examples of nonionic surfactants include ester type, ether type, ester-ether type, alkanolamide type, alkylglycoside type, and alcohol type nonionic surfactants.
[0027] These surfactants (c) may be used alone or in combination of two or more. The amount of the surfactant is not particularly limited and is appropriately determined depending on the cleaning power, but the amount is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, and most preferably 0.5 to 3 mass%. If the amount of the surfactant (c) is less than this range, the surface activity may be insufficient. If the amount is more than the above range, the surfactant becomes excessive and tends to remain on the surface as an adhesion inhibitor.
[0028] The dental cleaning material of the present invention can contain an organic solvent (d) to improve the solubility of deposits. Specific examples of organic solvents include alcohols such as methanol, ethanol, isopropyl alcohol, and glycerin; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ethers such as ethyl ether and tetrahydrofuran; esters such as ethyl acetate and ethyl formate; aromatic solvents such as toluene, xylene, and benzene; and non-aromatic hydrocarbon solvents such as hexane, heptane, and octane. Among these, alcohols and ketones are preferred from the viewpoint of solubility and storage stability, and ethanol, isopropyl alcohol, and acetone are particularly preferred.
[0029] These organic solvents may be used alone or in combination of two or more kinds. The amount of the organic solvent is not particularly limited and is appropriately determined depending on the solubility of the contaminant, but the amount is preferably 0.01 to 50 mass%, more preferably 0.1 to 50 mass%, and most preferably 1 to 20 mass%. If the amount of the organic solvent (d) is less than this range, the solubility of the contaminant may not be obtained. If the amount is more than the above range, the water-soluble silicate (b) may precipitate, resulting in reduced storage stability.
[0030] The dental cleaning material of the present invention may contain nanofibers (e) having a cellulose skeleton. The material of the nanofibers (e) having a cellulose skeleton is not particularly limited as long as it is a nanofiber having a cellulose skeleton shown in the following formula (Chemical formula 1), but preferably includes cellulose nanofibers obtained by pulverizing wood fibers obtained from wood to the nano order or partially modified cellulose nanofibers obtained by chemically modifying them, chitin nanofibers obtained from the shells and exoskeletons of crustaceans such as shrimp and crabs and insects, which are materials derived from chitin-containing organisms, or partially modified chitin nanofibers obtained by chemically modifying them, chitosan nanofibers made of β-1,4 poly-D-glucosamine obtained by deacetylating chitin obtained from the shells and exoskeletons of crustaceans such as shrimp and crabs and insects, or partially modified chitosan nanofibers obtained by chemically modifying them. Nanofibers having a cellulose skeleton are derived from natural products, so they have a small environmental impact in terms of production and disposal, and are highly biocompatible materials with extremely low toxicity.
[0031] [ka]
[0032] The fine fiber can be produced by mechanical fiberization or treatment with an oxidation catalyst, but is not particularly limited thereto. In addition, the fiber shows high viscosity when left to stand, but exhibits thixotropy, which means that the viscosity drops drastically when it flows. It has a specific gravity (1.0 to 1.5 g / cm3). 3 When the properties of the dental cleaning material of the present invention, such as viscosity and applicability, are adjusted by imparting thixotropy, the light specific gravity of the nanofibers themselves also works synergistically to make it difficult for sedimentation to occur and to maintain the properties for a long period of time.
[0033] The nanofiber (e) having a cellulose skeleton may be surface-treated to improve storage stability. For example, TEMPO oxidation, carboxymethylcellulose conversion, alkyl esterification, polymer coating, etc. can be used to change the hydrophobicity and surface charge of the surface.
[0034] The nanofiber (e) having a cellulose skeleton used in the present invention is not particularly limited as long as the fiber diameter is on the nano-order, but is preferably a fibrous material having a fiber diameter of 1 to 750 nm, and more preferably a fibrous material having a fiber diameter of 500 nm or less and an aspect ratio (fiber length / fiber diameter) of 100 or more.
[0035] The greatest advantage of incorporating nanofibers having a cellulose skeleton is that they improve cleaning properties. It is presumed that the adsorption of contaminants into the voids of the three-dimensional structure of the nanofibers and the moderate hydrophilicity of the cellulose skeleton contribute synergistically to cleaning properties. The nanofibers (e) having a cellulose skeleton used in the present invention may be used alone or in combination of two or more types. The amount of these nanofibers is preferably 0.1 to 30% by mass, more preferably 1 to 10% by mass. If the amount of nanofibers (e) having a cellulose skeleton is less than this range, no improvement in cleaning properties is obtained, and if the amount is more than the above range, the viscosity increases significantly and the operability is significantly reduced.
[0036] The dental cleaning material of the present invention may contain a chelating agent (f) in order to improve the cleaning property for ceramic materials. Specific examples of the chelating agent include polymerized phosphoric acid such as pyrophosphoric acid and triphosphoric acid, organic acids such as tartaric acid, succinic acid, malic acid, citric acid, and gluconic acid, ethylenediaminetetraacetic acid (EDTA), and salt compounds consisting of potassium, sodium, calcium, iron, copper, zinc, and the like. As the chelating agent, any known material can be used without limitation. Among these, sodium ethylenediaminetetraacetate, sodium gluconate, and copper gluconate are preferred from the viewpoint of cleaning property, and the amount of the chelating agent is preferably 0.01 to 5 mass%.
[0037] The dental cleaning material of the present invention may contain other ingredients as long as they do not impair the effects of the invention. For example, viscosity adjusters such as inorganic fine silica particles and polymeric thickeners, antibacterial agents such as heavy metal compounds, pyridine-quinoline and biguanide, colorants, fluorescent agents, fragrances, etc. may be blended. Other conventionally known additives and other ingredients may be added as necessary.
[0038] The method for preparing the dental cleaning material of the present invention is not particularly limited. An example of a general manufacturing method is a method in which each material is put into a container, mixed with a mixer or stirrer, and prepared into a uniform liquid. Another manufacturing method is a method in which the materials are mixed while applying shear force with a planetary centrifugal mixer. In the present invention, the dental cleaning material can be manufactured without any problems by the above manufacturing method.
[0039] The dental cleaning material of the present invention can also be used as a kit in combination with a dental material containing the acidic group-containing polymerizable monomer (g).
[0040] The dental material includes a dental bonding material, a dental primer, a dental resin cement, a dental self-adhesive resin cement, a dental composite resin, a dental self-adhesive composite resin, etc. After cleaning the surface to be adhered with the dental cleaning material of the present invention, adhesion can be performed using a dental material containing an acidic group-containing polymerizable monomer (g).
[0041] Specific examples of the acidic group-containing polymerizable monomer (g) that can be used in the dental material of the present invention include an acidic group-containing polymerizable monomer having a phosphoric acid group, an acidic group-containing polymerizable monomer having a pyrophosphoric acid group, a carboxylic acid group-containing polymerizable monomer, a phosphonic acid group-containing polymerizable monomer, and an acidic group-containing polymerizable monomer having a sulfonic acid group. In this specification, (meth)acrylate or (meth)acryloyl is used to collectively represent both an acryloyl group-containing polymerizable monomer and a methacryloyl group-containing polymerizable monomer.
[0042] Examples of the acidic group-containing polymerizable monomer having a phosphoric acid group include (meth)acryloyloxymethyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, and 6-(meth)acryloyloxyhexyl dihydrogen phosphate. phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyheptyl dihydrogen phosphate, ) Acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyeicosyl dihydrogen phosphate, di(meth)acryloyloxyethyl hydrogen phosphate, di(meth)acryloyloxybutyl hydrogen phosphate, di(meth)acryloyloxyhexyl hydrogen phosphate, di(meth)acryloyloxyoctyl hydrogen phosphate, di(meth)acryloyloxynonyl hydrogen phosphate Examples of the polymerizable monomers include, but are not limited to, acidic group-containing polymerizable monomers such as di(meth)acryloyloxydecyl hydrogen phosphate, 1,3-di(meth)acryloyloxypropyl-2-dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl 2'-bromoethyl hydrogen phosphate, and (meth)acryloyloxyethyl phenyl phosphonate.
[0043] Examples of the acidic group-containing polymerizable monomer having a pyrophosphate group include di[2-(meth)acryloyloxyethyl] pyrophosphate, di[3-(meth)acryloyloxypropyl] pyrophosphate, di[4-(meth)acryloyloxybutyl] pyrophosphate, di[5-(meth)acryloyloxypentyl] pyrophosphate, di[6-(meth)acryloyloxyhexyl] pyrophosphate, di[7-(meth)acryloyloxyheptyl] pyrophosphate, di[
[0113] Examples of polymerizable monomers containing an acidic group include, but are not limited to, di[8-(meth)acryloyloxyoctyl] pyrophosphate, di[9-(meth)acryloyloxynonyl] pyrophosphate, di[10-(meth)acryloyloxydecyl] pyrophosphate, di[12-(meth)acryloyloxydodecyl] pyrophosphate, tetra[2-(meth)acryloyloxyethyl] pyrophosphate, and tri[2-(meth)acryloyloxyethyl] pyrophosphate.
[0044] Examples of polymerizable monomers having a carboxylic acid group include (meth)acrylic acid, 2-chloro(meth)acrylic acid, 3-chloro(meth)acrylic acid, 2-cyano(meth)acrylic acid, aconitic acid, mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, citraconic acid, utraconic acid, 1,4-di(meth)acryloyloxyethylpyromellitic acid, 6-(meth)acryloyloxynaphthalene-1,2,6-tricarboxylic acid, 1- Butene 1,2,4-tricarboxylic acid, 3-butene 1,2,3-tricarboxylic acid, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, 4-(meth)acryloyloxybutyl trimellitic acid and its anhydride, 2-(meth)acryloyloxybenzoic acid, β-(meth)acryloyloxyethyl hydrogen succinate, β-(meth)acryloyloxyethyl 4-(meth)acryloyloxyethyl hydrogen maleate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, p-vinyl benzoic acid, 4-(meth)acryloyloxyethoxycarbonyl phthalic acid, 4-(meth)acryloyloxybutyloxycarbonyl phthalic acid, 4-(meth)acryloyloxyhexyloxycarbonyl phthalic acid, 4-(meth)acryloyloxyoctyloxycarbonyl phthalic acid, 4-(meth)acryloyloxydecyloxy Examples of the monomers include, but are not limited to, dicarbonylphthalic acid and its acid anhydrides, 5-(meth)acryloylaminopentylcarboxylic acid, 6-(meth)acryloyloxy-1,1-hexanedicarboxylic acid, 8-(meth)acryloyloxy-1,1-octanedicarboxylic acid, 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid, and 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid.
[0045] Examples of the acidic group-containing polymerizable monomer having a phosphonic acid group include, but are not limited to, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, and 10-(meth)acryloyloxydecyl-3-phosphonoacetate.
[0046] Examples of the acidic group-containing polymerizable monomer having a sulfonic acid group include, but are not limited to, 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, 2-sulfoethyl (meth)acrylate, 4-(meth)acryloyloxybenzenesulfonic acid, and 3-(meth)acryloyloxypropanesulfonic acid.
[0047] Among these acidic group-containing polymerizable monomers, it is preferable to use 10-methacryloyloxydecyl dihydrogen phosphate, 6-methacryloyloxyhexyl-3-phosphonoacetate, 4-methacryloyloxyethyl trimellitic acid and its anhydride, 4-acryloyloxyethyl trimellitic acid and its anhydride, etc.
[0048] These acidic group-containing polymerizable monomers may be used alone or in combination of two or more. The amount of these to be added is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the polymerizable monomer.
[0049] The dental material of the present invention may contain, for example, a non-acidic group-containing polymerizable monomer (a polymerizable monomer having no acidic group), a silane coupling agent, a (volatile) organic solvent, inorganic particles (inorganic filler), a pigment, and / or a polymerization catalyst, etc. For these components, conventionally known substances described in, for example, JP-A-2015-067594 and JP-A-2021-054815 can be used.
[0050] Next, an example of a cleaning method using the dental cleaning material of the present invention will be described. For example, the cleaning method using the dental cleaning material of the present invention can include a step of applying the dental cleaning material of the present invention to the adhesion surface of a prosthetic device and / or a tooth substance. In such a method, it is possible to effectively remove contaminants such as proteins from the adhesion surface using the dental cleaning material of the present invention.
[0051] Next, an example of a repair method using the kit of the present invention will be described. For example, the repair method using the kit of the present invention can include a step of treating the attachment surface of the prosthetic device and / or tooth substance with the dental cleaning material of the present invention, and a step of adhering a dental material containing an acidic group-containing polymerizable monomer (g) to the attachment surface of the prosthetic device and / or tooth substance. With such a method, it is possible to remove contaminants such as proteins from the attachment surface using the dental cleaning material of the present invention in clinical practice, and then apply the dental material.
[0052] The present invention also provides a method for visually confirming whether proteins have been removed. Specifically, the method includes the steps of attaching proteins to a test specimen made of, for example, dental hard resin, dental composite resin, dental metal, dental ceramics, dental porcelain, dental resin block, or tooth, staining the test specimen with a protein staining solution, and cleaning the surface of the test specimen with a dental cleaning material. With this method, an operator can visually confirm that proteins have been removed from the surface to be adhered by using the dental cleaning material of the present invention.
[0053] The present invention further provides a method for visually confirming that no protein remains. Specifically, the method includes the steps of attaching protein to a test specimen made of dental hard resin, dental composite resin, dental metal, dental ceramics, dental porcelain, dental resin block, or tooth, cleaning the surface of the test specimen with a dental cleaning material, and treating with a protein staining solution. With this method, the operator can visually confirm that no protein remains on the surface of the specimen cleaned with the dental cleaning material of the present invention. EXAMPLES
[0054] Examples of the present invention will be specifically described below, but the present invention is not limited to these examples.
[0055] [Production of the compositions described in the examples and comparative examples] The materials used in the examples and comparative examples and their abbreviations are shown below.
[0056] [Water (a)] DW: Distilled water
[0057] [Water-soluble silicate (b)] SOS: Sodium orthosilicate (molar ratio 0.5) SMS: Sodium metasilicate (molar ratio 1.0) PSI: Potassium silicate (molar ratio 2.0) SI3: Sodium silicate No. 3 (molar ratio 3.1) LOS: Lithium silicate (molar ratio 4.5)
[0058] [Surfactant (c)] <Cationic surfactants> ·BAC: Benzalkonium chloride <Amphoteric surfactants> CHAPS: 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate ·CAPB: Cocamidopropyl Betaine <Anionic surfactants> ·SLS: Sodium Lauryl Sulfate SDBS: Sodium dodecylbenzenesulfonate ·SMP: Sodium monododecyl phosphate <Nonionic surfactants> PSM: Polyoxyethylene (20) sorbitan monostearate ·OPE: Triton X-100 (t-octylphenoxypolyethoxyethanol, polyethylene glycol) ·PLE: Oxyethylene dodecyl ether
[0059] [Organic solvent (d)] EtOH: Absolute ethanol Ace: Acetone
[0060] [Nanofibers with a cellulose skeleton (e)] CNF: Cellulose nanofiber with average fiber diameter of 10-50 nm, 10% water dispersion
[0061] [Chelating agent (f)] CuGlu: Copper(II) gluconate EDTA: Sodium ethylenediaminetetraacetate
[0062] Acid group-containing polymerizable monomer (g) MDP: 10-methacryloyloxydecyl dihydrogen phosphate MHPA: 6-methacryloyloxyhexyl-3-phosphonoacetate MET: 4-Methacryloyloxyethyl trimellitic acid
[0063] [Thickener] <Organic thickener> ·XG: Xanthan gum <Hydrophilic silica filler> AR200: Aerosil 200 fumed silica manufactured by Nippon Aerosil Co., Ltd. (average particle size: 12 nm)
[0064] [Alkaline agent] ·NaOH: Sodium hydroxide KOH: Potassium hydroxide CMS: Calcium silicate (solubility in water at 25°C: 0.01g / 100mL)
[0065] 〔others〕 Bis-GMA: 2,2-bis(4-(3-methacryloyloxy-2-hydroxypropyl) (phenyl)propane UDMA: 2,2-bis(4-methacryloyloxyethoxyphenyl)propane HEMA: 2-hydroxyethyl methacrylate 14EG: Polyethylene glycol dimethacrylate (repeating number: 14) CQ: Camphorquinone DMBE: Ethyl dimethylaminobenzoate Inorganic particle A: Silica-zirconia filler (refractive index: 1.512, average particle size: 3.2 μm, silane-treated using 5 wt% 3-(methacryloyloxy)propyltrimethoxysilane) Inorganic particle B: Fluoroaluminosilicate glass (refractive index: 1.525, average particle size: 0.8 μm, silane-treated using 10 wt% 3-(methacryloyloxy)propyltrimethoxysilane)
[0066] The method for producing the dental cleaning material is described below.
[0067] All the materials shown in Table 1 were put into a wide-mouthed plastic container and mixed for 1 hour at 100 rpm using a mix rotor VMRC-5 to prepare a dental cleaning agent. The dental cleaning agent containing cellulose nanofiber was prepared by putting each material into a container using a planetary centrifugal mixer ARV-310 and kneading for 10 minutes at 1200 rpm. In Table 1, the mass% of each component is listed in parentheses after the abbreviation of each component, and water (a) is not considered from the total, but is the remainder after subtracting the components other than (a).
[0068] [Table 1]
[0069] The method for producing the dental material is described below.
[0070] Using a planetary centrifugal mixer ARV-310, the materials shown in Table 2 are added to a container, kneaded at 1200 rpm for 10 minutes, and then kneaded at 600 rpm for another 5 minutes under reduced pressure to 1 kPa. The resulting material is filled into a 1 mL Terumo syringe to be used as a dental material. In Table 2, the total amount of polymerizable monomers is 100 parts by mass, and the mass parts of each component are listed in parentheses after the abbreviation of each component.
[0071] [Table 2]
[0072] <Evaluation 1: Checking the cleansing effect on tooth surface> A test piece of a bovine central incisor embedded in epoxy resin was polished with waterproof abrasive paper #600 to remove the dentin surface. Then, artificial saliva (CaCl2: 1.2 mM, KH2PO4: 0.72 mM, KCl: 30 mM, HEPES: 50 mM, casein: 1000 μg / L) was applied to the dentin surface, left to stand for 10 minutes, then rinsed with water and dried. An appropriate amount of the cleaning agent listed in Table 1 was taken and rubbed with a brush on the surface for 10 seconds, rinsed with water and dried. The surface of a zirconia rod (φ4.0 mm) was sandblasted with alumina (50 μm) (0.2 MPa, 1 second), rinsed with water, dried, and coated with a zirconia adhesive primer (AZ Primer, Matsukaze). An appropriate amount of resin cement (Beauty Cem SA: Matsukaze) was applied to the adhesion surface of the zirconia rod, and the tooth substance and the zirconia rod were bonded. A load of 200N was applied vertically to the zirconia rod, and excess cement was removed. After that, the rod was irradiated with light for 10 seconds using a dental polymerization LED light irradiator (Penbright, Matsukaze), and the load was removed to obtain an adhesion test specimen (n=10). After immersion in water at 37°C for 24 hours, the specimen was immersed in a cold water phase of 4°C and a high temperature phase of 60°C for 60 seconds each using a thermal shock tester (manufactured by Thomas Scientific Instruments Co., Ltd.), and the cycle was repeated 5,000 times. After removing the specimen, the shear bond strength was measured at a crosshead speed of 1 mm / min using a universal testing machine (manufactured by Instron Co., Ltd.). When the bond strength at this time was compared with the bond strength to an adherend to which artificial saliva was not applied, the cleanability index was defined as follows. Cleanability index = (adhesive strength to a substrate after applying artificial saliva and cleaning with each dental cleaning material) / (adhesive strength to a substrate not applied with artificial saliva) A cleansability index of 80% or more was rated as A, 50% to less than 80% as B, and less than 50% as C. The bond strength to dentin to which artificial saliva had not been applied was 13.8 MPa.
[0073] <Evaluation 2: Confirmation of cleanability of prosthetic devices> A zirconia adherend (15mm x 15mm x 2.5mm) was polished with waterproof abrasive paper #600, the zirconia plane was cut off, the adherend surface was sandblasted with alumina (50μm) (0.2MPa, 1 second), then washed with water and dried. Then, artificial saliva (CaCl2: 1.2mM, KH2PO4: 0.72mM, KCl: 30mM, HEPES: 50mM, casein: 1000μg / L) was applied to the adherend surface of the zirconia, left to stand for 10 minutes, then washed with water and dried. An appropriate amount of the cleaning agent listed in Table 1 was taken and rubbed with a brush on the adherend surface for 10 seconds, washed with water and dried. The adherend surface of a stainless steel rod (φ4.5mm) was sandblasted with alumina (50μm) (0.4MPa, 1 second), then washed with water and dried, and a metal adhesive primer (Metal Link, Matsukaze) was applied. An appropriate amount of resin cement (Beauty Cem SA: Matsukaze) was applied to the surface of the stainless steel rod to bond the zirconia to the stainless steel rod. A load of 200N was applied vertically to the stainless steel rod, and excess cement was removed. After that, the rod was irradiated with light for 10 seconds using a dental polymerization LED light irradiator (Penbright, Matsukaze), and the load was removed to obtain an adhesion test specimen (n=10). After immersion in water at 37°C for 24 hours, the specimen was counted as immersion in a cold water phase of 4°C and a high temperature phase of 60°C for 60 seconds each using a thermal shock tester (manufactured by Thomas Scientific Instruments Co., Ltd.) and repeated 5,000 times. After removing the specimen, the tensile bond strength was measured at a crosshead speed of 1 mm / min using a universal testing machine (manufactured by Instron Co., Ltd.). When the adhesive strength at this time was compared with that to an adherend to which artificial saliva had not been applied, the above-mentioned cleanability index of 80% or more was judged to be A, 50% or more but less than 80% was judged to be B, and less than 50% was judged to be C. The adhesive strength to zirconia to which artificial saliva had not been applied was 13.1 MPa.
[0074] <Evaluation 3: Confirmation of irritation to living cells> A 3D human cultured cornea (LabCyte CORONA-MODEL, Japan Tissue Engineering) was used and evaluated according to OECD TG492. The operation was performed in a sterile environment, and the tools used were sterilized by autoclave. The cultured cornea was pre-cultured for 18 hours in a CO2 incubator (37°C, 5% CO2). 50 μL of the cleaning material listed in Table 1 was applied to the cultured cornea and left to stand for 1 minute, and then the cultured cornea was thoroughly washed with PBS. After the cultured cornea was cultured for 24 hours in a CO2 incubator (37°C, 5% CO2), WST-8 (CCK-8, Dojindo Chemical) was mixed with EBSS at a ratio of WST-8:EBSS = 1:10 and applied to the cultured cornea. After reacting for 4 hours, 200 μL of WST-8 was taken and transferred to a 96-well plate, and the absorbance at 450 nm and 650 nm was measured. The measured value was calculated from the absorbance using the following formula (1), and the viability was calculated using the following formula (2). A viability of 90% or more was judged as A, 40% or more but less than 90% as B, and less than 40% as C.
[0075] [(Formula 1)] Measurement value = (absorbance of sample (450 nm) - absorbance of sample (650 nm)) - (absorbance of blank (450 nm) - absorbance of blank (650 nm))
[0076] [(Formula 2)] Viable cell rate (%) = (average measured value of test substance / average measured value of PBS) x 100
[0077] <Evaluation 4: Checking the cleansing effect on tooth surface> A test piece of a bovine central incisor embedded in epoxy resin was polished with waterproof abrasive paper #600 to remove the dentin surface. Then, artificial saliva (CaCl2: 1.2mM, KH2PO4: 0.72mM, KCl: 30mM, HEPES: 50mM, casein: 1000μg / L) was applied to the dentin surface and left to stand for 10 minutes, then rinsed with water and dried. An appropriate amount of the cleaning agent listed in Table 1 was taken and rubbed with a brush on the surface for 10 seconds, then rinsed with water and dried. A double-sided tape with a hole of 4 mm in diameter was applied to the dentin, and a plastic mold (inner diameter 4 mm, height 2 mm) was fixed on it. The dental material listed in Table 2 was filled to about 0.5 mm on the adhesive surface, and then irradiated with light for 20 seconds using a photopolymerization irradiator (Penbright: made by Matsufu) to harden it. After filling it further to 2 mm, a glass plate was pressed from above, and then irradiated with light for 20 seconds using a photopolymerization irradiator (Penbright: made by Matsufu) to harden it. The glass plate and mold were removed to prepare adhesion test specimens (n=10). The adhesion test specimens were immersed in 37°C water for 24 hours, and then immersed in a 4°C cold water phase and a 60°C high temperature phase for 60 seconds each were counted as one time using a thermal shock tester (made by Thomas Scientific Instruments), and the test specimens were repeated 5000 times. After removing the test specimens, the shear bond strength was measured using a universal testing machine (made by Instron) at a crosshead speed of 1 mm / min. When the adhesive strength at this time was compared with that to an adherend to which artificial saliva had not been applied, the above-mentioned cleanability index of 80% or more was judged as A, 50% or more but less than 80% as B, and less than 50% as C. The adhesive strengths to dentin to which artificial saliva had not been applied were 10.8 MPa, 13.0 MPa, 12.8 MPa, and 15.3 MPa for dental materials 1 to 4, respectively.
[0078] <Evaluation 5: Confirmation of cleanability of prosthetic devices> A zirconia adherend (15mm x 15mm x 2.5mm) was polished with waterproof abrasive paper #600 to remove the zirconia surface, and the adherend surface was sandblasted with alumina (50μm) (0.2MPa, 1 second), washed with water, and dried. Then, artificial saliva (CaCl2: 1.2mM, KH2PO4: 0.72mM, KCl: 30mM, HEPES: 50mM, casein: 1000μg / L) was applied to the zirconia adherend surface, left to stand for 10 minutes, washed with water, and dried. An appropriate amount of the cleaning agent listed in Table 1 was taken and rubbed on the adherend surface with a brush for 10 seconds, washed with water, and dried. A double-sided tape with a hole of 4 mm in diameter was attached to the zirconia, and a plastic mold (inner diameter 4 mm, height 2 mm) was fixed on it. The dental material listed in Table 2 was filled to about 0.5 mm on the adhesive surface, and the material was hardened by irradiating light for 20 seconds using a photopolymerization irradiator (Penbright: made by Matsufu). After filling the material to 2 mm, a glass plate was pressed from above, and then irradiated with light for 20 seconds using a photopolymerization irradiator (Penbright: made by Matsufu). The glass plate and mold were removed to prepare adhesion test specimens (n=10). The adhesion test specimens were immersed in 37°C water for 24 hours, and then immersed in a 4°C cold water phase and a 60°C high temperature phase for 60 seconds each were counted as one time using a thermal shock tester (made by Thomas Scientific Instruments), and the test specimens were repeated 5,000 times. After removing the test specimen, the shear bond strength was measured at a crosshead speed of 1 mm / min using a universal testing machine (made by Instron). When the adhesive strength at this time was compared with the adhesive strength to an adherend to which artificial saliva had not been applied, the above-mentioned cleanability index of 80% or more was judged as A, 50% or more but less than 80% as B, and less than 50% as C. The adhesive strengths to zirconia to which artificial saliva had not been applied were 18.4 MPa, 20.3 MPa, 17.1 MPa, and 25.9 MPa for dental materials 1 to 4, respectively.
[0079] [Table 3]
[0080] As shown in Table 3, when cleaning materials described in cleaning materials 1 to 31 (Examples 1 to 31) were used to treat tooth tissue and prosthetic devices with protein, the cleaning index was 50% or more, and it was confirmed that the cleaning materials had excellent cleaning properties against adhesion inhibitors derived from living bodies such as saliva. In addition, when the cleaning materials described in cleaning materials 1 to 31 (Examples 1 to 31) were applied to a 3D human cultured cornea, it was confirmed that the cell viability was 40% or more. From this, it was confirmed that the cleaning materials described in the examples have low irritation. On the other hand, cleaning materials 32 to 38 (Comparative Examples 1 to 7) do not have a high cleaning index and a high cell viability at the same time. Cleaning materials 32 and 35 to 37 have a high cell viability rate, but have low cleaning performance against tooth tissue and prosthetic devices with protein attached. Cleaning materials 33 and 34 containing potassium hydroxide and sodium hydroxide have cleaning performance, but are highly irritating to living bodies.
[0081] [Table 4]
[0082] As shown in Table 4, it was confirmed that when the kits described in Kits 1 to 16 (Examples 32 to 47) were used on tooth structure and prosthetic devices with protein attached, an excellent cleansing index of 80% or more was shown. On the other hand, it was confirmed that Kits 17 to 24 (Comparative Examples 8 to 15) had a low cleansing index and poor cleansing ability on tooth structure and prosthetic devices with protein attached.
[0083] <Evaluation 5: Evaluation method A for demonstration kits> Artificial saliva (CaCl2: 1.2mM, KH2PO4: 0.72mM, KCl: 30mM, HEPES: 50mM, casein: 1000μg / L) was applied to the surface of the zirconia, left to stand for 10 minutes, then washed with water and dried. After that, it was immersed in a CBB staining solution for protein detection (Rpid CBB KANTO 3S, KANTO CHEMICAL CO., INC.) for 1 hour, washed with water, and dried to obtain a protein-stained test specimen. An appropriate amount of cleaning material 1 listed in Table 1 was taken from this test specimen, and the surface was rubbed with a brush for 10 seconds, washed with water, dried, and the surface was observed. As a result, the surface of the protein-stained test specimen shown in Figure 1(A) after treatment with cleaning material 1 changed as shown in Figure 1(B), and it was possible to visually confirm that the stained protein had been removed.
[0084] <Evaluation 6: Evaluation method B for demonstration kits> Artificial saliva (CaCl2: 1.2mM, KH2PO4: 0.72mM, KCl: 30mM, HEPES: 50mM, casein: 1000μg / L) was applied to the surface of the zirconia, left to stand for 10 minutes, then washed with water and dried. After masking half A of the zirconia specimen with tape, an appropriate amount of cleaning material 2 listed in Table 1 was taken on the unmasked half B, rubbed with a brush on the surface for 10 seconds, washed with water and dried. After that, the tape was removed, and the specimen was immersed in a CBB staining solution for protein detection (Rpid CBB KANTO 3S, KANTO CHEMICAL CO., INC.) for 1 hour, washed with water, dried, and the surface was confirmed. As a result, as shown in Figure 2, it was confirmed that the staining of the surface to which the cleaning material was applied was clearly lower than that of the surface to which the cleaning material was not applied, and that the protein had been removed. [Industrial Applicability]
[0085] The dental cleaning material according to the present invention can be used for cleaning dental prosthetic devices and abutment teeth.
Claims
1. A dental cleaning material comprising water (a) and a water-soluble silicate (b).
2. 2. The dental cleaning material according to claim 1, which has a pH of 10 to 13.
3. The water-soluble silicate (b) is 2 O (M is an alkali ion) and SiO 2 2. The dental cleaning material according to claim 1, which is an alkali metal salt of silicic acid comprising:
4. The water-soluble silicate (b) is 2 O and SiO 2 Molar ratio (SiO 2 / M 2 4. The dental cleaning material according to claim 3, wherein O) is 0.5 to 4.
0.
5. The dental cleaning material according to claim 1 , further comprising a surfactant (c).
6. The dental cleaning material according to claim 5, further comprising 0.01 to 10 mass % of a surfactant (c).
7. The dental cleaning material according to claim 1 , further comprising an organic solvent (d).
8. The dental cleaning material according to claim 7, further comprising 0.01 to 50 mass % of an organic solvent (d).
9. The dental cleaning material according to claim 1 , further comprising nanofibers (e) having a cellulose skeleton.
10. The dental cleaning material according to claim 9, further comprising 0.1 to 30 mass% of nanofibers (e) having a cellulose skeleton.
11. The dental cleaning material according to claim 1 , further comprising a chelating agent (f).
12. The dental cleaning material according to claim 11, further comprising 0.01 to 5 mass % of a chelating agent (f).
13. A kit comprising a combination of the dental cleaning material according to any one of claims 1 to 12 and a dental material containing an acidic group-containing polymerizable monomer (g).
14. A cleaning method comprising the step of applying the dental cleaning material according to any one of claims 1 to 12 to a surface of a prosthesis and / or a tooth to be adhered thereto.
15. A step of treating a surface of a prosthesis and / or a tooth with the dental cleaning material according to any one of claims 1 to 12; and adhering a dental material containing an acidic group-containing polymerizable monomer (g) to a surface of the prosthesis and / or tooth to be adhered.
16. A step of attaching a protein to a test specimen made of a dental hard resin, a dental composite resin, a dental metal, a dental ceramic, a dental porcelain, a dental resin block, or a tooth; staining with a protein stain; A method for visually confirming that the protein has been removed by cleaning the surface of the test specimen using a dental cleaning material.
17. A step of attaching a protein to a test specimen made of a dental hard resin, a dental composite resin, a dental metal, a dental ceramic, a dental porcelain, a dental resin block, or a tooth; cleaning the surface of the test specimen with a dental cleaning material; and treating the sample with a protein staining solution to visually confirm that no protein remains.
Citation Information
Patent Citations
Readdin unit of original
JP1981007559A
Dental cleaning material
JP2020083872A